Enhancing Safety Culture in Vocational Education: Insights from Industrial Workshops - Muhammad Sayuti; Harry Agus Susanto; Noviatun Hasanah; Muhammad Kunta Biddinika; Wadiyo; Meshack Opwora; Arasinah Kamis; Na'ilir Rokhmah (Universitas Muhammadiyah Surakarta, 2024)
This study analyzes the condition of industrial workshops related to Occupational Safety and Health (K3) equipment and workshop regulations according to supervisors' and industrial instructors’ views. The availability of K3 equipment and workshop rule standards are considered important due to the development of students' industrial cultural character toward fostering job readiness. The results show the K3 culture in the Prakerin industry tends to be positive. It is found the necessity to focus on commitment and management style as the key to improving safety culture. Although K3 document is considered sufficient, workers’ and students’ response vary in K3 culture of Prakerin. This indicates the need for improving understanding of safety in Prakerin. Based on the F-test, the availability of documents and worker culture simultaneously affect the student's K3 culture. Although the t-test shows that work safety documents have no significant effect, worker safety culture has a very significant influence on student work safety culture. It concludes that the adoption of K3 culture by workers in industry influenced the K3 culture of Prakerin students. This study recommends to exploring influence of industrial environment on student character by evaluating various industry, for understanding student’ character building and job readiness of vocational graduates.